Paciente de sexo masculino de 58 años de edad con cirrosis hepática en estadio 3 y desnutrición proteico calórica leve - De La Cruz Díaz, Angie Mirella (2021)
The present clinical case is a 58-year-old male patient who attended a medical consultation due to progressive weight loss, loss of appetite, jaundice, fatigue, edema in the upper and lower limbs and abdominal distention, the patient did not refer to a personal pathological history and relatives, you do not smoke, but if you drink alcohol for more than 20 years, The objective of this work is to improve the nutritional status of the patient through nutritional intervention, the nutritional status of the patient was evaluated with the anthropometric, biochemical, clinical and dietetic method, where the patient presented a body mass index of 18.2kg / m2 when diagnosed with malnutrition and a progressive weight loss of 17.3% in 3 months, in addition to this I present in the laboratory data hypertriglyceridemia, increased liver transaminases, hypoalbuminemia, hypoproteinemia, hyperbilirubinemia and low hemoglobin, in addition, in the physical examination, the patient presented a thin frame, jaundice, edema in the upper and lower extremities and ascites, in the diet the patient presented a 24-hour recall of hypocaloric with 51% adequacy, hypoglucid 28%, hypoprotein 55% and hypo lipid with 57%. A dietary and nutritional plan was established according to the pathological state and requirements of the patient, a diet of 2300 calories was prescribed hyperprotein, hypo-fat, and hypo-sodium distributed in 5 meal times, moderate volume, warm temperature and soft consistency, and a follow-up to control was possible. of the diet therapy plan and monitoring of the patient considering all the parameters of the nutritional, anthropometric, biochemical, clinical and dietary evaluation where we observe in the 3rd month the evolution of the patient that has improved.